2017
DOI: 10.1371/journal.pone.0188302
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo effects of intraocular and intracranial pressures on the lamina cribrosa microstructure

Abstract: There is increasing clinical evidence that the eye is not only affected by intraocular pressure (IOP), but also by intracranial pressure (ICP). Both pressures meet at the optic nerve head of the eye, specifically the lamina cribrosa (LC). The LC is a collagenous meshwork through which all retinal ganglion cell axons pass on their way to the brain. Distortion of the LC causes a biological cascade leading to neuropathy and impaired vision in situations such as glaucoma and idiopathic intracranial hypertension. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 34 publications
3
66
0
1
Order By: Relevance
“…We are not aware of other studies characterizing LC beam microstructural properties and their relationship with the LC beam width. Several studies, for example in vivo imaging using optical coherence tomography, 18 , 19 , 46 49 and ex vivo studies using serial block face imaging, 50 second harmonic generated (SHG) imaging, 5 , 6 , 51 54 have quantified LC trabecular beam and pore morphology, including the diameters, but have reported no information on collagen microstructural characteristics, such as the crimp. Accurate measurement of collagen crimp requires high angular and spatial resolutions, otherwise the orientation information will encode both anisotropy and crimp.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of other studies characterizing LC beam microstructural properties and their relationship with the LC beam width. Several studies, for example in vivo imaging using optical coherence tomography, 18 , 19 , 46 49 and ex vivo studies using serial block face imaging, 50 second harmonic generated (SHG) imaging, 5 , 6 , 51 54 have quantified LC trabecular beam and pore morphology, including the diameters, but have reported no information on collagen microstructural characteristics, such as the crimp. Accurate measurement of collagen crimp requires high angular and spatial resolutions, otherwise the orientation information will encode both anisotropy and crimp.…”
Section: Discussionmentioning
confidence: 99%
“…15 Quantitative measurement of nerve fiber layer thickness and ONH structure with OCT 16 now permits detailed examination of LC substructure and its positional movements with change in IOP and intracranial pressure. [17][18][19][20] For digital analysis to be useful in clinical practice and research, automated methods are needed that require minimal observer input.…”
Section: Discussionmentioning
confidence: 99%
“…42 In addition to IOP, Wang and coworkers showed that CSF pressure affects the structure of the LC as measured by its thickness and fenestration pore size. 196 Changes in the pressure-gradient force at the LC (i.e., TLPD) are dependent on the IOP and orbital CSF pressure. While, in a conventional sense, elevated IOP and ICP are critical parameters in glaucoma and papilledema, respectively, alterations in TLPD may be particularly important in cases of NTG and ODE in the setting of normal ICP (Fig.…”
Section: Definition and Physiological Implicationsmentioning
confidence: 99%